Bridging Indigenous Knowledge and Islamic Environmental Ethics: Empirical Evidence from Customary Law and Sustainable Practices in Rural Indonesia - Hanafi, Syawaluddin (Al-'Adl, 2026)
This article aims to analyze local wisdom as a foundation for ecotheology through theoretical and empirical examinations of the customary law of Tompo Bulu Village. The research is grounded in the phenomenon of a tree-planting tradition institutionalized within customary norms and village regulations, and consistently practiced by the community at every moment of birth and marriage. The study employs a qualitative method using a socio-legal and interdisciplinary perspective that integrates the theories of environmental maqāṣid, ecological justice, and Islamic ecotheology. Data were collected through observation, interviews, and analysis of customary legal documents as well as village regulations. The findings indicate that the tree-planting tradition functions not only as an environmental conservation practice but also as a normative mechanism that internalizes the values of tawḥīd (divine unity), amānah (trust), and human responsibility as khalīfah (stewards). This practice contributes to the maintenance of ecological functions, food security, and the sustainability of resources for future generations. Furthermore, the customary law of Tompo Bulu reflects principles of ecological justice through the distribution of conservation responsibilities, recognition of local knowledge, and protection of intergenerational rights. These findings affirm that the integration of local wisdom, environmental maqāṣid, and Islamic ecotheology can serve as a model for environmental governance that is contextual, participatory, and sustainable. Therefore, strengthening customary law grounded in ecological spirituality holds strategic relevance for sustainable development and the advancement of environmental law in Indonesia.